ZikaPLAN: Zika Preparedness Latin American Network. - Wilder-Smith, A; Preet, R; Renhorn, K; Ximenes, R; Rodrigues, L; Solomon, T; Neyts, J; Lambrechts, L; Willison, H; Peeling, R; Falconar, A; Precioso, A; et al. (Taylor and Francis, 2017)
The ongoing Zika virus (ZIKV) outbreak in Latin America, the Caribbean, and the Pacific Islands has underlined the need for a coordinated research network across the whole region that can respond rapidly to address the current knowledge gaps in Zika and enhance research preparedness beyond Zika. The European Union under its Horizon 2020 Research and Innovation Programme awarded three research consortia to respond to this need. Here we present the ZikaPLAN (Zika Preparedness Latin American Network) consortium. ZikaPLAN combines the strengths of 25 partners in Latin America, North America, Africa, Asia, and various centers in Europe. We will conduct clinical studies to estimate the risk and further define the full spectrum and risk factors of congenital Zika virus syndrome (including neurodevelopmental milestones in the first 3 years of life), delineate neurological complications associated with ZIKV due to direct neuroinvasion and immune-mediated responses in older children and adults, and strengthen surveillance for birth defects and Guillain-Barré Syndrome. Laboratory-based research to unravel neurotropism and investigate the role of sexual transmission, determinants of severe disease, and viral fitness will underpin the clinical studies. Social messaging and engagement with affected communities, as well as development of wearable repellent technologies against Aedes mosquitoes will enhance the impact. Burden of disease studies, data-driven vector control, and vaccine modeling as well as risk assessments on geographic spread of ZIKV will form the foundation for evidence-informed policies. While addressing the research gaps around ZIKV, we will engage in capacity building in laboratory and clinical research, collaborate with existing and new networks to share knowledge, and work with international organizations to tackle regulatory and other bottlenecks and refine research priorities. In this way, we can leverage the ZIKV response toward building a long-term emerging infectious diseases response capacity in the region to address future challenges.